2018
DOI: 10.1007/s00296-018-4069-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA values in children with rheumatic carditis: a preliminary study

Abstract: MicroRNAs (miRNAs) are fine regulators of gene expression which participate in the regulation of almost every phase of cell physiology, including development of immune cells and adjustment of immune response. In the studies with in vitro/in vivo model systems, specific miRNAs are revealed to have various roles in cardiovascular development and physiological functions. Furthermore, some studies have been done to understand the role of miRNAs about myocarditis, heart failure and coronary artery diseases. miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Adhikari et al [ 19 ] also provided evidence that miR-16 was decreased in the circulation of end-stage heart failure patients. The study of Gumus et al [ 20 ] demonstrated that plasma hsa-miR-16-5p was 1.46-fold lower expressed in the patients with rheumatic carditis than that of controls. In line with these studies, we also validated miR-16 was downregulated in the plasma and PBMCs of CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adhikari et al [ 19 ] also provided evidence that miR-16 was decreased in the circulation of end-stage heart failure patients. The study of Gumus et al [ 20 ] demonstrated that plasma hsa-miR-16-5p was 1.46-fold lower expressed in the patients with rheumatic carditis than that of controls. In line with these studies, we also validated miR-16 was downregulated in the plasma and PBMCs of CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been observed that inhibition of miR‐16 defends against acute myocardial infarction in rats . Recent literature has shown that miR‐16‐5p is visibly downregulated in children with rheumatic carditis . In the analysis of He et al, miR‐16 played an important role in hypertensive heart diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we focused on the role of miR‐16‐5p in the regulation of senescence via lncRNA MEG3. Previous studies have demonstrated that miR‐16‐5p correlates with multiple pathophysiological processes, including tumors, 49,50 nerve injury, 51 rheumatic carditis, 52 diabetic nephropathy 51 and longevity 29 . In addition, overexpression of miR‐16‐5p reduced p21 and p16 expression and the number of SA‐β‐gal staining cells, whereas down‐regulation of miR‐16‐5p contributed to the senescence phenotype, suggesting that miR‐16‐5p could regulate the senescence process of tumor cells.…”
Section: Discussionmentioning
confidence: 99%